The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1242/bio.029009
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics and respiration within cells with increased open pore cytoskeletal meshes

Abstract: The cytoskeletal architecture directly affects the morphology, motility, and tensional homeostasis of the cell. In addition, the cytoskeleton is important for mitosis, intracellular traffic, organelle motility, and even cellular respiration. The organelle responsible for a majority of the energy conversion for the cell, the mitochondrion, has a dependence on the cytoskeleton for mobility and function. In previous studies, we established that cytoskeletal inhibitors altered the movement of the mitochondria, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…We have advanced our previous work in which we published whole cell mitochondrial tracking based on fluorescence live imaging. 17,18 We have expanded our method to now track mitochondria networking in whole cells using PBMCs freshly obtained from subjects and easily compare networking between PBMCs obtained from healthy subjects and PBMCs obtained from subjects with sepsis, an acute care illness. We have demonstrated that the methodology is accessible within a clinically meaningful time frame, thus illustrating the translational strength of our method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have advanced our previous work in which we published whole cell mitochondrial tracking based on fluorescence live imaging. 17,18 We have expanded our method to now track mitochondria networking in whole cells using PBMCs freshly obtained from subjects and easily compare networking between PBMCs obtained from healthy subjects and PBMCs obtained from subjects with sepsis, an acute care illness. We have demonstrated that the methodology is accessible within a clinically meaningful time frame, thus illustrating the translational strength of our method.…”
Section: Discussionmentioning
confidence: 99%
“…We preprocessed raw image files in ImageJ using an approach previously presented. 17,18 Briefly, time-lapse images were first convolved using the 5×5 edge-detection filter given in. Next, images were converted to the frequency domain using a Fast Fourier Transform (FFT) in ImageJ, and subjected to a bandpass filter ranging from 2 pixels (~0.3 μm with our resolution) to 100 pixels (~16 μm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the obviously visible rounding of the cells, whole cell volumes in PV-MDCK cells (− 30%) were decreased approximately proportional to the decrease in mitochondrial mass (− 40%). This effect might be linked to the mitochondrial Ca 2+ buffering capacity, shown to be implicated in cytoskeleton dynamics [ 66 ] and also to the intracellular distribution of mitochondria, which strongly depends on mitochondria–cytoskeleton interactions [ 45 , 50 ]. In line with our findings, blocking of mitochondrial Ca 2+ uptake in MCU-knockdown cells results in an increased circularity coefficient [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed a specialized protocol to establish the respiratory capacities at various complexes providing more detailed respiratory activity at complex (C) I, II, III, IV. Our published manuscripts describe these methods in further detail in regard to injections with specific concentrations [12,25,28].…”
Section: Mitochondrial Bioenergetics and Dynamics Methodsmentioning
confidence: 99%